FATP4 inactivation in cultured macrophages attenuates M1- and ER stress-induced cytokine release via a metabolic shift towards triacylglycerides - Zhang, Yuling; Wu, Ning; Gan-Schreier, Hongying; Xu, Feng; Tuma-Kellner, Sabine; Staffer, Simone; Seeßle, Jessica; Merle, Uta; Chamulitrat, Walee (Biochemical journal, 2021)
Fatty acid transport protein 4 (FATP4) belongs to a family of acyl-CoA synthetases which activate long-chain fatty acids into acyl-CoAs subsequently used in specific metabolic pathways. Patients with FATP4 mutations and Fatp4-null mice show thick desquamating skin and other complications, however, FATP4 role on macrophage functions has not been studied. We here determined whether the levels of macrophage glycerophospholipids, sphingolipids including ceramides, triacylglycerides, and cytokine release could be altered by FATP4 inactivation. Two in vitro experimental systems were studied: FATP4 knockdown in THP-1-derived macrophages undergoing M1 (LPS + IFNγ) or M2 (IL-4) activation and bone marrow-derived macrophages (BMDMs) from macrophage-specific Fatp4-knockout (Fatp4M−/−) mice undergoing tunicamycin (TM)-induced endoplasmic reticulum stress. FATP4-deficient macrophages showed a metabolic shift towards triacylglycerides and were protected from M1- or TM-induced release of pro-inflammatory cytokines and cellular injury. Fatp4M−/− BMDMs showed specificity in attenuating TM-induced activation of inositol-requiring enzyme1α, but not other unfolded protein response pathways. Under basal conditions, FATP4/Fatp4 deficiency decreased the levels of ceramides and induced an up-regulation of mannose receptor CD206 expression. The deficiency led to an attenuation of IL-8 release in THP-1 cells as well as TNF-α and IL-12 release in BMDMs. Thus, FATP4 functions as an acyl-CoA synthetase in macrophages and its inactivation suppresses the release of pro-inflammatory cytokines by shifting fatty acids towards the synthesis of specific lipids.
Accepted manuscript online: 26 April 2021
Version of record online: 18 May 2021
Gesehen am 06.09.2021